Lucky Luke. 10, Tortillas for the Daltons - Goscinny, 1926-1977.; Morris, 1923-; Spear, Luke (Canterbury, Kent [England] : Cinebook, 2008)
As the Daltons are transferred to a Mexican prison, robbers attack and kidnap the brothers without knowing it; once they realize their mistake, they decide to hang the four brothers until Joe offers to share his secrets of organized crime, and Lucky Luke attempts a rescue.
First published: Paris: Dargaud Editeur, c1971, under title: Lucky Luke: Tortillas pour les Daltons.
Translated from the French.
3.4
3-6.
3-6
Keywords: Dalton Gang -- Comic books, strips, etc. -- Juvenile fiction; Dalton Gang -- Fiction; Dalton Gang -- Comic books, strips, etc. -- Fiction; Cowboys -- Comic books, strips, etc -- Juvenile fiction; Criminals -- Comic books, strips, etc -- Juvenile fiction; Lucky Luke (Fictitious character) -- Comic books, strips, etc -- Juvenile fiction; Cartoons and comics; Cowboys -- Fiction; Criminals -- Fiction; Lucky Luke (Fictitious character). -- Fiction; Comic books, strips, etc; Cowhands -- Comic books, strips, etc -- Fiction; Criminals -- Comic books, strips, etc -- Fiction; Graphic novels; Lucky Luke (Fictional character) -- Comic books, strips, etc -- Fiction; Western comic books, strips, etc; West (U.S.) -- Fiction; Graphic novels; Western comic books, strips, etc